2017
DOI: 10.1111/desc.12456
|View full text |Cite
|
Sign up to set email alerts
|

Power in methods: language to infants in structured and naturalistic contexts

Abstract: Methods can powerfully affect conclusions about infant experiences and learning. Data from naturalistic observations may paint a very different picture of learning and development than those based on structured tasks, as illustrated in studies of infant walking, object permanence, intention understanding, and so forth. Using language as a model system, we compared the speech of 40 mothers to their 13-month old infants during structured play and naturalistic home routines. The contrasting methods yielded unique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
133
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 140 publications
(148 citation statements)
references
References 54 publications
5
133
0
1
Order By: Relevance
“…By mirroring the results of previous laboratory‐based observations (Pereira et al., ; Yu & Smith, ), the current study adds to a body of evidence that has found parallels between data obtained from structured observations in the laboratory and data obtained from free‐flowing observations in the home (Adolph et al., ; Bornstein, Haynes, Painter, & Genevro, ; Tamis‐LeMonda et al., ). We suggest that the reason the current home‐based findings on referential visual clarity mimic those obtained in the laboratory is because, as our work shows, toddlers' visual ecology is largely determined by the unique physical attributes of toddlers' bodies.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…By mirroring the results of previous laboratory‐based observations (Pereira et al., ; Yu & Smith, ), the current study adds to a body of evidence that has found parallels between data obtained from structured observations in the laboratory and data obtained from free‐flowing observations in the home (Adolph et al., ; Bornstein, Haynes, Painter, & Genevro, ; Tamis‐LeMonda et al., ). We suggest that the reason the current home‐based findings on referential visual clarity mimic those obtained in the laboratory is because, as our work shows, toddlers' visual ecology is largely determined by the unique physical attributes of toddlers' bodies.…”
Section: Discussionsupporting
confidence: 83%
“…Previous studies that have explicitly compared parent–infant interactions in the home to those in the laboratory do indeed show key differences (Belsky, ; Stevenson, Leavitt, Roach, Chapman, & Miller, ). Compared to in the home, parents in the laboratory talked more (Stevenson et al., ; see also Tamis‐LeMonda, Kuchirko, Luo, Escobar, & Bornstein, ), were more attentive (Belsky, ), and were more responsive to their children's behavior (Belsky, ). Additionally, although parents were not explicitly instructed to teach their toddlers the object names in these studies, parents were provided with and taught the set of novel names (e.g., “dodi”) ahead of time.…”
Section: Parent Object Naming: the Toddler's Viewmentioning
confidence: 99%
“…The analyses of simulated environments show that adding new contexts changes the type‐token curve, leading to more rapidly increasing types as a function of tokens. These simulations indicate that we do not just need to understand the distribution of words in parent talk but also the distribution of contexts in children's lives, as well as the talk that characterizes those different contexts (Tamis‐LeMonda et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Methodologically, the same measure of a characteristic applied at different times yields higher stability estimates of the characteristic, whereas different measures yield lower stability estimates (minimally on account of method variance; ): Switching from maternal report at 2 years to testing methods at 5 years attenuates stability of children's language between those time points . Some measures (e.g., self‐report) tend to show greater stability than others (e.g., observation; ). The shorter the interassessment interval, the greater the likelihood of continuity and stability (the Guttman “simplex”; ).…”
Section: Moderation Of Developmental Consistency and Changementioning
confidence: 99%